The Influence of Educational Robotics in STEM Integrated Learning and the Development of Computational Thinking Abilities - Sadik, Muhammad Aqil; Budiyanto, Cucuk Wawan; Yuana, Rosihan Ari (Jurnal Nasional Pendidikan Teknik Informatika : JANAPATI, 2024)
Currently, educational robotics are becoming an important trend in education, introducing transformative elements into the classroom to improve the learning environment. Educational robotics in STEM-integrated learning can develop computational thinking skills. Educational robotics has begun to be widely adopted and is expected to enhance computational thinking skills in early childhood education, secondary school, and higher education. In this study, we examine the role of educational robotics in integrated STEM learning environments and its impact on the development of computational thinking. The method used was a systematic literature review. Initial search returned 541 articles from various journals indexed in Scopus. Subsequently, 351 articles published between 2020 2024 were sorted out, and only 37 articles were included in the final analysis. Studies show that educational robotics effectively promotes STEM education and facilitates the development of computational thinking skills. The importance of project-based learning and the integration of STEM disciplines in educational robotics inform educators and policymakers about the potential benefits of educational robotics in promoting STEM education and developing computational thinking skills.